Zalesienia a sukcesja wtórna - Krawczyk, Robert (Leśne Prace Badawcze, 2014)
Secondary succession is a long and complicated natural process returning forests to post agricultural lands, whereas afforestation is an attempt to speed up this process by planting trees. Massive afforestation in the twentieth century brought an increase in forest area in Poland along with management problems in these areas due to disturbances caused by root diseases. Therefore it appears necessary to employ successional processes more fully in order to create sustainable forest ecosystems.